Genetic and phenotypic heterogeneity in pattern dystrophy. Issue 9 (19th August 2005) - Francis, P J; Schultz, D W; Gregory, A M; Schain, M B; Barra, R; Majewski, J; Ott, J; Acott, T; Weleber, R G; Klein, M L
Abstract : Background: The pattern dystrophies (PD) represent a clinically heterogeneous family of inherited macular diseases frequently caused by mutations in the peripherin/ RDS gene. Most previous studies have detailed the clinical findings in single families, making it difficult to derive data from which progression and visual outcome can be generalised. Methods: Families were ascertained and clinically evaluated including angiography and electrophysiology where appropriate. Results: In each of the six families with autosomal dominant PD, a mutation in the peripherin/ RDS gene was identified, including a novel Cys250Phe variant. These data suggest that the condition is characterised by the accumulation of yellow to grey subretinal flecks, followed by pigmentary change accompanied by patches of chorioretinal atrophy. Subsequently, 50% (16/32) of individuals with PD developed poor central vision because of chorioretinal geographic atrophy or subretinal neovascularisation. The risk of these complications appears to increase with age. Conclusion: PD should not necessarily be considered a benign condition. Instead, patients should be counselled that there is a significant chance of losing central vision in their later years. Some elderly patients with probands showing PD may be misdiagnosed with age related macular degeneration owing to the phenotypic similarities between these conditions in the advanced state.